VARIASI VERBA PENGARUH PENANDA PERSONA DAN KALA PADA BAHASA-BAHASA DI TANAH PAPUAPAPUA - Mantiri, Grace Janice M. (Hasta Wiyata, 2024)
Papuan area known as ethnic and language variety. In language aspect, Papuan languages have uniqueness. The most unique is have person and tense marker in verb. The present of person and tense marker making many verb forms. In addition, there are two types of languages. The types are Austronesian and Non-Austronesian, and two types of sentence structure are SOP and SPO. This research aims to describe verb forming of Papuan languages because person and tense markers. And also, to compare verb forming process of Papuan Austronesian and Non-Austronesian, and more SOP and SPO languages structure.